ChemInform Abstract: Rhodium‐Catalyzed Acyloxy Migration of Propargylic Esters in Cycloadditions, Inspiration from the Recent "Gold Rush". Issue 13 (18th March 2013) - Shu, Xing‐Zhong; Shu, Dongxu; Schienebeck, Casi M.; Tang, Weiping
Abstract Review: 69 refs.